Temperature and pressure dependent creep stress analysis of spherical shell - Pathania, Devinder Singh; Verma, Gaurav (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, we have studied the temperature and pressure dependent creep stress analysis of spherical shell. The review is critical to enhance the warm resistance of spherical shells in high-temperature conditions. The effect of different parameters was studied and it was noticed that the parameter n has a significant influence on the creep stresses and strain rates. Creep stresses and strain rates are ascertained on the premise of summed up strain measures and Seth`s transition hypothesis.
Keywords: creep; temperature; pressure; spherical shell; stress; strains